PENGARUH TERAPI ZIKIR TERHADAP TINGKAT DEPRESI PADA PASIEN GAGAL GINJAL YANG MENJALANI HAEMODIALISA - Himawan, Fatchurozak; Suparjo, Suparjo; Cuciati, Cuciati (Universitas Muhammadiyah Magelang, 2020)
Hemodialysis for patients with chronic kidney failure can cause anxiety that can change at any time and can end up being depressed. Dzikir provides a sense of calm, eliminates sadness and raises motivation for a better life and is able to reduce anxiety and depression. This study aims to determine the effect of morning and evening dhikr on the level of depression in kidney failure patients undergoing hemodialysis at Kardinah Tegal General Hospital. The research method used is quantitative research with a Quasi-experiment with (Non-Equivalent Control Group) Pretest Posttest design. The total sample of 40 respondents consisted of 20 respondents in the control group and 20 respondents in the intervention group. Sampling uses a technique purposive sampling. An Instrument for measuring depression with the Beck Depression Inventory (BDI) II. The results of the study showed a decrease in the level of depression in the intervention group with a Wilcoxon pre-post difference test value of 0.007. with an average score drop of 4.95 points. From 20 respondents there were 15 respondents who experienced a decrease in score with an average decrease in score of 11.83 points and 5 respondents experienced an increase in an average of 5 points. There was no effect of decreasing the level of depression in the control group with a Wilcoxon pre-post difference test value of 0.268. There was an increase in depression scores of 10 respondents and 9 respondents experienced a decrease with an average of 6.75 points. It can be concluded that dhikr therapy in the morning is not the only factor that can reduce the level of depression in hemodialysis respondents with kidney failure.